2019
DOI: 10.1136/bmjopen-2018-024797
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the frequency and appropriateness of vitamin D testing after the introduction of new Medicare criteria for rebates in Australian general practice: evidence from 1.5 million patients in the NPS MedicineInsight database

Abstract: ObjectivesTo assess changes in the frequency of vitamin D testing and detection of moderate/severe vitamin D deficiency (<30 nmol/L) among adults after the introduction of new Medicare Benefits Schedule (MBS) rebate criteria (November 2014), and their relationship to sociodemographic and clinical characteristics.DesignDynamic (open) cohort studySettingPrimary careParticipantsAbout 1.5 million ‘active’ patients aged 18+ years visiting a general practitioner and included in the National Prescribing Service Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
0
26
2
1
Order By: Relevance
“…Our findings differ to that of Gonzalez-Chica et al., 8 in that we found that the detection rate of patients with severe deficiency (serum 25(OH)D levels <25 nmol/L) was significantly reduced from 2.6% before to 1.6% of patients tested after the intervention; Gonzalez-Chica et al. found some 5.4% of patients at the slightly higher level of serum 25(OH)D <30 nmol/L before compared to 6.4% afterwards.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings differ to that of Gonzalez-Chica et al., 8 in that we found that the detection rate of patients with severe deficiency (serum 25(OH)D levels <25 nmol/L) was significantly reduced from 2.6% before to 1.6% of patients tested after the intervention; Gonzalez-Chica et al. found some 5.4% of patients at the slightly higher level of serum 25(OH)D <30 nmol/L before compared to 6.4% afterwards.…”
Section: Discussioncontrasting
confidence: 99%
“…It could be argued that such outcomes are difficult to measure, but that is not always the case as indicated by this study and that of Gonzalez et al. 8…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Other studies have gone one step further in trying to improve the allocation of vitamin D tests in practice. An Australian study showed that a strategy to tackle the number of tests does not necessarily correlate with more appropriate testing [ 32 ]. Another study focused on improving vitamin D supplementation in aged care without measuring vitamin D levels, but care facilities still identified physicians’ beliefs and attitudes related to blood tests as a barrier to routine supplementation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] For example, increased testing for vitamin D has been observed in several countries, and even though guidelines do not advocate or even discourage screening for vitamin D deficiency. [5][6][7][8][9][10] In Switzerland, a recent database analysis found increasing MLT use in general practice but comprehensive population-based studies are still lacking. 11 Such insights, however, are necessary to advance the understanding of potential overuse of MLT.…”
Section: Introductionmentioning
confidence: 99%